Familiarity Affects Entrainment of EEG in Music Listening - Yuiko Kumagai; Mahnaz Arvaneh; Toshihisa Tanaka; Toshihisa Tanaka (Frontiers in Human Neuroscience, 2017)
Music perception involves complex brain functions. The relationship between music and brain such as cortical entrainment to periodic tune, periodic beat, and music have been well investigated. It has also been reported that the cerebral cortex responded more strongly to the periodic rhythm of unfamiliar music than to that of familiar music. However, previous works mainly used simple and artificial auditory stimuli like pure tone or beep. It is still unclear how the brain response is influenced by the familiarity of music. To address this issue, we analyzed electroencelphalogram (EEG) to investigate the relationship between cortical response and familiarity of music using melodies produced by piano sounds as simple natural stimuli. The cross-correlation function averaged across trials, channels, and participants showed two pronounced peaks at time lags around 70 and 140 ms. At the two peaks the magnitude of the cross-correlation values were significantly larger when listening to unfamiliar and scrambled music compared to those when listening to familiar music. Our findings suggest that the response to unfamiliar music is stronger than that to familiar music. One potential application of our findings would be the discrimination of listeners' familiarity with music, which provides an important tool for assessment of brain activity.